2001
DOI: 10.1097/00006254-200108000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Practice Trends in Outpatient Obstetrics and Gynecology: Findings of the Collaborative Ambulatory Research Network, 1995–2000

Abstract: After completion of this article, the reader will be able to define what the Collaborative Ambulatory Research Network (CARN) involves, describe how CARN obtains its data, and summarize some of the findings of CARN from the years 1995 to 2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Members of CARN typically do not differ from large random samples of ACOG fellows and junior fellows in practice on our other survey instruments. 9 Although our study may be subject to nonresponse bias, the findings should be reliable. The typical response rate in these surveys ranges from 35% to 60% and, at 55%, our response rate was at the high end of expected participation.…”
Section: Demographicsmentioning
confidence: 66%
See 1 more Smart Citation
“…Members of CARN typically do not differ from large random samples of ACOG fellows and junior fellows in practice on our other survey instruments. 9 Although our study may be subject to nonresponse bias, the findings should be reliable. The typical response rate in these surveys ranges from 35% to 60% and, at 55%, our response rate was at the high end of expected participation.…”
Section: Demographicsmentioning
confidence: 66%
“…Members of CARN represent each of the 10 ACOG districts, and typically have not differed from large random samples of ACOG Fellows and Junior Fellows in Practice on our other survey instruments. 9 On the basis of similar studies conducted by ACOG, where preliminary power analyses indicated that the minimum number of responses needed to ensure significant effect sizes was approximately 100, our sample size was deemed sufficient. 10 All non-respondents received a second mailing of the questionnaire four weeks after the first mailing.…”
Section: Methodsmentioning
confidence: 99%
“…However, CARN members are a representative sample (by age, gender, and geographic location) of the ACOG membership, of which over 90% of obstetrician-gynecologists in the US are members. Previous analyses assessing whether responses from CARN members differ from those of ACOG members in general [14] have concluded that there are few, if any, differences between samples.…”
Section: Discussionmentioning
confidence: 99%
“…Six hundred two recipients were members of the Collaborative Ambulatory Research Network (CARN), which is a group of practicing obstetrician-gynecologists who volunteer to participate in survey research. (12) The other 200 recipients were randomly selected ACOG members who had not received a survey from ACOG in the previous 2 years. Other ACOG studies which surveyed both CARN members and a random sample of ACOG members have found that CARN members had been in practice longer than non-CARN members, but that there were no differences between groups in terms of distribution of responses to the survey questions.…”
Section: Methodsmentioning
confidence: 99%